(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article is devoted to analyzing the formation and development of gender sociology in the works of domestic scientists. It examines key areas of contemporary research, in particular the problems of gender inequality in the labour market, women’s participation in political life, the transformation of gender roles during periods of military conflict and migration processes, as well as cultural interpretations of gender identity and stereotypes. It is shown that gender sociology in Ukraine is developing under the influence of global trends, while preserving national specificity and contemporary socio-political challenges. The importance of European integration processes and the UN Sustainable Development Goals as essential benchmarks for research on gender equality is emphasised. The authors of the works analysed in the article combine empirical sociological methods with qualitative cultural approaches, which allows for a comprehensive view of the problem. The article highlights the role of socio-economic transformations and democratisation processes in shaping new perceptions of gender roles in Ukrainian society. It analyses the influence of international organisations and regulatory acts on developing national gender policy and practices to ensure equal opportunities. Particular attention is paid to the interconnection between gender studies and current challenges, in particular war, internal displacement of the population, increased civic activism, and changing social roles. The conclusion is made about the need for further systematization of scientific achievements, interdisciplinary integration, and the development of effective mechanisms to ensure gender equality in all spheres of public life. Prospects for further research lie in studying the processes of institutionalisation of social practices, analysing the effectiveness of state gender policy, and comparing the Ukrainian experience with international models. Such research will contribute to the development of domestic science and Ukraine’s integration into the global scientific space, providing a deeper understanding of the patterns of gender democracy formation.